Factors Affecting Income in Tirta Boalemo Regency Regional Water Company (PDAM) - Elandri Bakari; Imam Mashudi; Syamsinah (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This research has a problem formulation, namely What is the level of income in the Regional Water Supply Company Tirta, Boalemo Regency. The objectives to be achieved in this study are to determine the level of income in the Regional Drinking Water Company (PDAM) of Boalemo Regency. This research uses descriptive research with quantitative and qualitative research approaches by assigning the Head of the Public Administration and Finance Section and the Head of the Sub Division of Subscription Relations at the Regional Water Company (PDAM) of Boalemo Regency as sources of information. As well as data collection methods are observation, interview, and documentation. The results of this study indicate that in the analysis of the factors that influence the increase in income at the local water company (PDAM) in Boalemo Regency, the income is quite significant, seen in the revenue realization and income. Customers of PDAM Tirta, Boalemo Regency The number of subscribers has a very big influence on the company's revenue as seen from the number of customers in Boalemo Serta Regency The profitability of PDAM Boalemo Regency revenue has increased quite significantly.